Efficacy and safety of herbal formulas with the function of gut microbiota regulation for gastric and colorectal cancer: A systematic review and meta-analysis - Xu, Bowen; Wang, Xinmiao; Wang, Heping; Cao, Luchang; Ge, Yuansha; Yuan, Bo; Gao, Ruike; Li, Jie (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Currently, gastric cancer (GC) and colorectal cancer (CRC) are the most common causes of cancer-related mortality worldwide. Gut microbiota is closely related to the occurrence of gastrointestinal cancer and the efficacy of chemotherapy. This study is aimed to evaluate the efficacy and safety of herbal formulas with the function of regulating gut microbiota (HFRGM) in the treatment of GC and CRC. Methods: A comprehensive search was performed on eight electric databases and two clinical trial registries from their initiation to January, 2022. Randomized controlled trials (RCTs) studying the therapeutic effects of HFRGM were included. We used Stata 16 for data synthesis and assessed quality of the synthesized evidence in GRADE approach. Results: Fifty-three RCTs involving 4478 patients were included. These trials involve seven herbal formulas that could regulate gut microbiota of Bifidobacterium, Lactobacillus, Escherichia coli, Bacteroides, and Enterococcus faecalis. The meta-analysis results were subgrouped to three different stages in gastrointestinal cancer: (1) For perioperative stage, HFRGM combined with conventional therapy could shorten the time to bowel sound recovery, the time to first flatus, and the duration of hospitalization in GC. There were no significant differences in outcomes of gastrointestinal function recovery and adverse events (AEs) in CRC. (2) For postoperative patients, combine with adjuvant chemotherapy, HFRGM could decrease the incidence of AEs in GC; boost KPS improvement rate, and decrease the incidence of AEs in CRC. (3) For advanced stage, HFRGM can significantly improve the ORR and DCR, KPS improvement rate, and decrease the incidence of AEs in GC. There were no significant differences in ORR and DCR, but it can improve KPS response rate, decrease the incidence of AEs in CRC. Conclusion: This study indicates that herbal formulas have a positive effect in all stages of gastrointestinal cancer. It could promote the recovery of postoperative gastrointestinal function, increase tumor response, improve performance status, and reduce the incidence of AEs. To further support the conclusion and better understand the role of gut microbiota in the treatment of gastrointestinal cancer, more rigorously designed, large-scale, and multicenter RCTs that focus on herbal formulas and gut microbiota are needed in the future.